y = 3(x + 4)^2 + 31
Step-by-step explanation:
We can convert the given quadratic equation into its vertex form by completing the square:
y = 3x^2 + 24x + 43
= 3(x^2 + 8x) + 43
= 3(x^2 + 8x + 4) + 31
= 3(x + 4)^2 + 31
This is the vertex form of the given quadratic equation with (-4, 31) as its vertex
If the points are scattered it’s no correlation
Answer:
It's just c
Step-by-step explanation:
That's what corresponding angles look like? I don't really know how to explain this. Sorry!
Answer:
12, 17, 24
Step-by-step explanation:
To find the first 3 terms, substitute n = 1, 2, 3 into the rule, that is
T₁ = 1² + 2(1) + 9 = 1 + 2 + 9 = 12
T₂ = 2² + 2(2) + 9 = 4 + 4 + 9 = 17
T₃ = 3² + 2(3) + 9 = 9 + 6 + 9 = 24